Religious or Non-Religious: TM in American Courts - Baird, Robert D. (Journal of Dharma, 1982)
The Transcendental Meditation movement is one among numerous movements in the U. S. today that is firmly rooted in Indian religio- philosophical traditions. However, TM consistently seeks to be understood simply as a technique and its spokesmen strongly deny that it is a religion. It is the credibility of this disavowal that has enabled TM to get support for its programmes from correctional institutions run by the state, state legislatures, departments of the federal government and local school officials.